Understanding of Healthy and Halal Additive Criteria for MSME Actors in Gresik Regency: Pemahaman Kriteria Bahan Tambahan yang Sehat dan Halal Pada Pelaku UMKM di Kabupaten Gresik - Nuniek Herdyastuti; Tukiran; Titik Taufikurohmah; Sari Edi Cahyaningrum; Ratih Dewi Saputri (Universitas Lancang Kuning, 2023)
Gresik Regency is very rich in its typical food involving UMKM. They were still use many synthetic additives such as dyes, flavors, and flavorings with the aim of beautifying the appearance and strengthening the taste. The continuous use of synthetic additives can interfere with health and also many have not met halal criteria. They do not know or apathetic to the dangers posed by the use of additives, so it is necessary to carry out socialization related to healthy and halal ingredients. The methods used are counseling and practice of identifying ingredients based on nutritional composition and critical ingredients and conducting evaluations through response questionnaires. The results showed that 36.4% of participants did not know how to identify halal products; 36.5 – 45.5% still use synthetic additives and 90.9% their knew the effects of using synthetic additives. The practice showed that UMKM do not understand critical materials so that follow-up needs on understanding critical materials.